Enabling Stable Lithium Metal Anode through Electrochemical Kinetics Manipulation - Han, Yehu; Jie, Yulin; Huang, Fanyang; Chen, Yawei; Lei, Zhanwu; Zhang, Genqiang; Ren, Xiaodi; Qin, Lianjie; Cao, Ruiguo; Jiao, Shuhong (Advanced functional materials, 2019)
The surface morphology of Li metal anode significantly dictates the stability and safety of Li metal batteries. The key parameters for morphological control and causes for dendritic growth of Li anode are still not clear. Although the plating kinetics is generally believed to be associated with Li growth habits, the detailed models are still not well defined. In this work, the temperature effect on the stability and efficiency of Li anode is systematically investigated in a variety of electrolyte composition for Li metal batteries. A dendrite‐free growth mechanism is observed, and a high Coulombic efficiency up to ≈99.4% in Li||Cu cells is achieved by tuning the deposition behaviors at elevated temperatures. The results provide insights into the Li dendrite growth mechanism and general principle for developing stable Li anode. The temperature effect on lithium metal anodes is demonstrated in a variety of aprotic electrolytes. High Coulombic efficiency and dendrite‐free growth modes can be achieved in an ether‐based electrolyte at elevated temperature. The electrochemical kinetics of lithium plating/stripping processes are significantly improved at high temperature.